Dinamika Pengelolaan Ruang Publik Terpadu Ramah Anak: Sebuah Proyek Perkotaan Berkelanjutan? - Paulus Bagus Sugiyono; Raphaella Dewantari Dwianto (Faculty of Social Science, Universitas Negeri Malang, 2021)
This article aims to explain the historical dynamics of RPTRA’s management in Jakarta during few recent years. Notwithstanding common functionalist approach, such as Aji et al. (2016) and Sutanto (2018), this article attempts to employ another approach. It tries to portray RPTRA not as a space that “is already being there”, used by city residents to do their various activities, but as a space that is dynamically as well as continuously formed by several factors, for instance economy, politics, and culture. The theoretical concept that is taken as an analysis framework is the concept of space, offered by Henri Lefebvre. This research employs analytic-descriptive qualitative method, such as literature reading. Some articles related with RPTRA which were published within last five years are collected, read, and analysed. This research itself was conducted between February until June 2021. The result of the research states that there are three socio-political disruptions which happened during the historical dynamics of RPTRA’s management. Those related with accommodation of residents’ activities, the dynamics of political situation, and pandemic Covid-19. The Lefebvrian analysis of space shows that there is often friction between city planning and management made by the government and the hope and expectation of city residents. The former indicates abstract space, while the latter indicates social space as were conceived by Lefebvre. For the sake of sustainable management, the participation of civil society must be included continuously. Furthermore, government itself must take political policy discreetly and not for mere political hegemony.